The Implementation of Word Search Puzzle with Numbered-Heads Together Strategy to Increase Students’ Vocabulary Mastery - Nurlaely Hidayati; Dwi Rukmini; Rahayu Puji Haryanti (English Education Journal, 2024)
Considering the significance of vocabulary mastery in language acquisition, this research addressed students' challenges in vocabulary learning. Particularly, this study evaluates the implementation of Word Search Puzzles combined with the Numbered-Heads Together (NHT) strategy to improve students’ vocabulary mastery. A mixed-methods approach was utilized, by combining quantitative and qualitative methods. The research involved pre-tests, treatments using Word Search Puzzles and NHT, post-tests, observations, questionnaires, and interviews. The results show that there is a significant improvement in students' vocabulary mastery, with an increase in scores from pre-test to post-test. Also, most of the students expressed enjoyment and interest in the new teaching methods. It can be concluded that the use of Word Search Puzzles and the NHT strategy positively impact students’ vocabulary mastery. Consider the effectiveness of the applied strategies, it is suggested for educators, especially English teachers, to consider to application of Word Search Puzzle with Numbered-Heads Together strategy into classroom practices.